2017
DOI: 10.1016/j.mimet.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficient differentiation of Corynebacterium striatum , Corynebacterium amycolatum and Corynebacterium xerosis clinical isolates by multiplex PCR using novel species-specific primers

Abstract: A multiplex-PCR (mPCR) assay was designed with species-specific primers which generate amplicons of 226bp, 434bp and 106bp for differentiating the species C. striatum, C. amycolatum, and C. xerosis, respectively. mPCR results were 100% in agreement with identifications achieved by 16S rRNA and rpoB gene sequencing and by VITEK-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Several studies have shown that C. amycolatum infections are often misidentified by culturing and subsequent phenotypic analysis of the isolates, making it difficult to implement appropriate therapeutic interventions ( Funke et al, 1996 ; Zinkernagel et al, 1996 ; Wauters et al, 1998 ; Soltan Mohammadi et al, 2013 ). In this sense, it is essential to define better phenotypic and genetic markers that could improve the identification of pathogenic nonlipophilic members of the genus Corynebacterium , including C. amycolatum ( Santos et al, 2017 , 2018 ). C. amycolatum can be clearly distinguished from C. xerosis and C. imitans by means of MALDI-TOF mass spectrometry using the MALDI Biotyper system ( Alibi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that C. amycolatum infections are often misidentified by culturing and subsequent phenotypic analysis of the isolates, making it difficult to implement appropriate therapeutic interventions ( Funke et al, 1996 ; Zinkernagel et al, 1996 ; Wauters et al, 1998 ; Soltan Mohammadi et al, 2013 ). In this sense, it is essential to define better phenotypic and genetic markers that could improve the identification of pathogenic nonlipophilic members of the genus Corynebacterium , including C. amycolatum ( Santos et al, 2017 , 2018 ). C. amycolatum can be clearly distinguished from C. xerosis and C. imitans by means of MALDI-TOF mass spectrometry using the MALDI Biotyper system ( Alibi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…which are difficult-to-differentiate from C. amycolatum in phenotypic tests, particularly C. xerosis ( Santos et al, 2018 ). Besides, through comparative genomics we were able to identify specific target genes that can render reliable identification of C. striatum , C. amycolatum and C. xerosis clinical isolates, by multiplex PCR ( Santos et al, 2017 ). More recently, different studies have been demonstrating the added value of whole-genome analyses to improve species circumscription in the genus Corynebacterium , including the study by Dover and collaborators ( Dover et al, 2021 ) which proposes a new phylogenomic-based classification of the genus Corynebacterium , based on previous studies ( Huson and Bryant, 2006 ), encompassing 19 phylogenetic groups; C. amycolatum belongs to the newly proposed group M, that also includes isolates of C. xerosis and C. freneyi ( Dover et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) has been applied to perform accurate species-level identification of Corynebacterium spp. clinical isolates, but this technology is not yet fully accessible to clinical microbiology laboratories in resource-limited settings [17]. Also, MALDI-TOF requires pure cultures as starting material, which precludes rapid diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Within recent years there has been a considerable increase in the number of literature data reporting non-diphtherial corynebacteria (also known as diphtheroids) as the causative agents of opportunistic and nosocomial infections in humans (De Miguel-Martinez et al 1996;Yoon et al 2011;Bernard 2012b;Nhan et al 2012;Qin et al 2017;Santos et al 2017;Kang et al 2018). These bacteria are members of the microbiota of the skin and mucous membranes (Qin et al 2017;Santos et al 2017;Kang et al 2018). The potential association between coryneforms and clinical infections can be attributed to immunosuppression, severe underlying medical disorders or invasive procedures (Nhan et al 2012;Cacopardo et al 2013;Kimura et al 2017;Qin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Within recent years there has been a considerable increase in the number of literature data reporting non-diphtherial corynebacteria (also known as diphtheroids) as the causative agents of opportunistic and nosocomial infections in humans (De Miguel-Martinez et al 1996;Yoon et al 2011;Bernard 2012b;Nhan et al 2012;Qin et al 2017;Santos et al 2017;Kang et al 2018). These bacteria are members of the microbiota of the skin and mucous membranes (Qin et al 2017;Santos et al 2017;Kang et al 2018).…”
Section: Introductionmentioning
confidence: 99%